2018
DOI: 10.3171/2016.11.jns162433
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm wall enhancement on magnetic resonance imaging as a risk factor for progression of unruptured vertebrobasilar dissecting aneurysms after reconstructive endovascular treatment

Abstract: ABBREVIATIONS 3D-TOF = 3D time of flight; CI = confidence interval; DSA = digital subtraction angiography; EVT = endovascular treatment; FSE = fast spin-echo; HRMRI = high-resolution MRI; IMH = intramural hematoma; MRA = MR angiography; OR = odds ratio; TSE = turbo spin-echo; VBDA = vertebrobasilar dissecting aneurysm. SUBMITTED September 20, 2016 Department of Neurosurgery, the First Affiliated Hospital, Nanchang University, Nanchang, Jiangxi Province, China OBJECTIVE The recurrence rate of vertebrobasilar di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Regular physical examination including MRI and MRA for the patients with high risk factor (such as family history of GVBAs), might be an optional method for discovery of these lesions early. Moreover, the assessment of HRMRI in GVBAs patients might be identified the high-risk patients with evidence of progression on imaging (8). However, future studies are necessary to clarify these points and provide optimal treatment for patients with GVBAs and further advancements are necessary to provide optimal treatment for patients with GVBAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical examination including MRI and MRA for the patients with high risk factor (such as family history of GVBAs), might be an optional method for discovery of these lesions early. Moreover, the assessment of HRMRI in GVBAs patients might be identified the high-risk patients with evidence of progression on imaging (8). However, future studies are necessary to clarify these points and provide optimal treatment for patients with GVBAs and further advancements are necessary to provide optimal treatment for patients with GVBAs.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were recommended to undergo a 6-month angiographic follow-up, and a magnetic resonance (MR) angiogram or computed tomography angiogram performed annually thereafter. Any aneurysm that displayed an increasing percentage of contrast filling of the aneurysmal sac on follow-up angiography or presented with more than 1-mm enlargement on MR imaging was considered an unfavorable angiographic outcome ( 8 ). The occlusion rate (<90%) for the aneurysms with flow diverter and re-patency of parent artery for the aneurysms with internal trapping were defined as unfavorable angiographic outcomes ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, wall enhancement has not yet been validated by using histopathologic data; therefore, its inflammatory nature remains speculative (17,18). One may consider the possibility that, although many studies (7,8,10,15,19,20) have reported that vessel wall enhancement of aneurysms may be a marker for instability, CAWE may be the mere consequence of slow flow artifact near the wall. Furthermore, we acquired images a short time after contrast agent injection, meaning that slow flowing, T1-shortened blood near the wall could cause wall enhancement-like flow artifacts.…”
Section: Discussionmentioning
confidence: 99%
“… In our experience, follow-up angiography alone does not adequately predict the outcome whereas HRMRI is a more useful means of following these lesions [ 38 ]. We have also found and reported that aneurysm wall enhancement on HRMRI predicts instability of an intracranial aneurysm [ 39 ]. HRMRI will be performed on patients enrolled in the UIA follow-up cohort at the 20 participating centers and HRMRI-identified aneurysm wall enhancement assessed as a possible predictor of UIA rupture.…”
Section: Methods and Designmentioning
confidence: 93%